Enhancing Dental Health Knowledge Through The Combination of Storytelling and Interactive Activities at TK Sepuluh November - Maharani, Aulia Dwi; Paramita, Ayulistya; Lestari, Gunarti Dwi; Bunga Fauzia (Denta Journal Kedokteran Gigi, 2026)
Background: Dental health in preschool children is an important aspect that should be introduced early. However, cognitive limitations and short attention spans at this age require educational methods appropriate to their developmental stage. Pojok Sikat Gigi is an activity that consists of various health promotion and preventive strategies carried out at TK Sepuluh November Surabaya, targeting teachers, parents, and students. One strategy is dental health education through storytelling, using hand puppets and interactive activities. Objective: This study aimed to determine the effectiveness of dental health education with storytelling and interactive activities on improving preschool students’ knowledge of dental health. Method: 34 students aged between 5-7 were the sample in this research. This was a pre-experimental research with a pre- and post-test design. The pretest score was measured through a Q&A session before education. The posttest score was measured by asking students to write down their answers on a piece of paper, guided by the researcher who read the same questions. The pre- and post-test knowledge scores were compared using the Wilcoxon statistical test to assess whether there was a significant difference after the educational intervention. Results: The mean pretest score was 2.24, and the posttest score was 5 (maximum score was 5). The Wilcoxon test value was sig=0.00<0.05, meaning that there was a significant difference between the scores before and after education. Conclusion: The storytelling method and interactive activities are effective in improving preschool students’ knowledge of dental health.